PUBLIC HEALTH HAZARDS ASSOCIATED WITH NATURALLY OCCURRING TOXINS IN LEGUME SEEDS - RAPID DETECTION AND CHARACTERIZATION OF A LECTIN FROM A KOREAN CULTIVATED KIDNEY BEAN (PHASEOLUS VULGARIS L.) - Nciri, Nader; Shin, Taesub; Cho, Namjun (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The delicacy of kidney beans is highly appreciable but, at the same time, their toxicity has raised an alarming concern. In this regard, more public awareness is needed about bean poisoning. Methods: This work aimed at promptly investigating the chemical and biological properties of a lectin derived from a Korean cultivar of the common bean (Phaseolus vulgaris L.). Results: Sodium dodecyl sulfate-polyacrylamide gel electrophoresis revealed the presence of two major polypeptide bands around 31.00 kDa. Hemagglutination assay and Ouchterlony double immunodiffusion technique confirmed the presence of lectin in dry seeds. Conclusion: It was evident that the Korean bean cultivar contains biologically active lectins, which may pose a risk to the consumer if the beans are eaten in raw or undercooked state.